2017
DOI: 10.1016/j.ajpath.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Increase in Intestinal Epithelial Tight Permeability Is Mediated by Toll-Like Receptor 4/Myeloid Differentiation Primary Response 88 (MyD88) Activation of Myosin Light Chain Kinase Expression

Abstract: Lipopolysaccharides (LPSs) are a major component of the Gram-negative bacterial cell wall and play an important role in mediating intestinal inflammatory responses in inflammatory bowel disease. Although recent studies suggested that physiologically relevant concentrations of LPS (0 to 1 ng/mL) cause an increase in intestinal epithelial tight junction (TJ) permeability, the mechanisms that mediate an LPS-induced increase in intestinal TJ permeability remain unclear. Herein, we show that myosin light chain kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(138 citation statements)
references
References 55 publications
(55 reference statements)
8
129
0
1
Order By: Relevance
“…TLR-mediated signaling pathways are involved in regulating intestinal epithelial barrier integrity [60]. In our study, NE infection significantly increased IFN-γ and IGF-2 mRNA levels and downregulated TLR-4, adaptor protein tumor necrosis factor receptor (TNFR)-associated factor 6 (TRAF-6), NF-κB, TNFSF15, TLR-activating negative regulators TOLLIP, PI3K and SOCS-6 and EGFR mRNA expression in the jejunum compared with the unchallenged control.…”
Section: Discussionmentioning
confidence: 55%
“…TLR-mediated signaling pathways are involved in regulating intestinal epithelial barrier integrity [60]. In our study, NE infection significantly increased IFN-γ and IGF-2 mRNA levels and downregulated TLR-4, adaptor protein tumor necrosis factor receptor (TNFR)-associated factor 6 (TRAF-6), NF-κB, TNFSF15, TLR-activating negative regulators TOLLIP, PI3K and SOCS-6 and EGFR mRNA expression in the jejunum compared with the unchallenged control.…”
Section: Discussionmentioning
confidence: 55%
“…ethanol administration and the presence of bacterial products such as LPS, since both are TLR4 agonists. Recent studies suggest that physiologically relevant concentrations of LPS (0–1 ng·mL −1 ) cause an increase in colonic epithelial TJ permeability that was mediated by the up‐regulation of myosin light‐chain kinase in a mechanism dependent on the TLR‐4/MyD88 signal transduction pathway (Nighot et al ., ). Both long‐term (Tamai et al ., ) and acute ethanol administration (Tamai et al ., ) enhance small intestine absorption of LPS, and we demonstrated that this also occurs after repeated binge episodes (Antón et al ., and current study).…”
Section: Discussionmentioning
confidence: 97%
“…In humans, dysfunction of intestinal epithelial barrier leads to increased permeability of intestinal mucosa, subsequent translocation of intestinal pathogenic bacteria or toxins, which in turn aggravates the damage of intestinal barrier integrity, resulting in local intestinal or systemic disease such as inflammatory bowel diseases, multiple organ dysfunction syndromes, and sepsis (Yoseph et al, 2016;Meng et al, 2017). LPS, a representative biological marker of systemic microbial translocation, plays an important role in the initiation and development of intestinal epithelial barrier dysfunction (Nighot et al, 2017). Caco-2 cells infected with LPS are widely used as an in vitro model for evaluating intestinal barrier function in humans.…”
Section: Discussionmentioning
confidence: 99%